Exploring the Relationship Between Entry-Level Master's Program Class Size and the Number of Graduate Credits Offered and Aggregate NBCOT Pass Rates - Scott Truskowski (Scholarworks @ WMU, 2016)
The AOTA and ACOTE have discussed a transition to a mandated entry-level clinical doctorate degree (Harvison, 2013). Following the move to the entry-level master's degree in 2007, the overall national pass rate on the national certification examination fell from 88% in 2006 to 77% by 2009 (Harvison, 2011; Harvison, 2012). This study sought to determine if the number of graduate credits offered or the class size of an entry-level master's program impacts student outcomes on the national certification examination. Publicly available data was mined from all accredited entry-level master's programs. Data were imported into the SPSS for statistical analysis. The results indicated no significant relationship between the number of graduate credits offered and pass rates (p = 0.919) or between average class size and pass rates (p = 0.640). Further study is warranted to determine if there are any curricular characteristics that can be used to predict student performance on the national certification examination.